Difference Analysis of Accounting Profit and Fiscal Profit on Profit Persistence - Dini Angraini (JEKAMI Journal of Accounting, 2022)
The purpose of this study was to determine the effect of the difference in accounting profit and fiscal profit on earnings persistence in the research study of PT Charoen Popkhand Indonesia Tbk. In this study using a quantitative approach with data collection techniques using financial statement analysis. The data analysis technique used in this research is descriptive, namely the comparison, change, growth between the difference in accounting profit and fiscal profit to earnings persistence in 2014 to 2019. The results showed that (1) the difference in accounting profit and fiscal profit (time difference / temporary) at PT Charoen Popkhand Indonesia Tbk for 4 years for the largest negative fiscal correction was in 2018, namely Rp. 69.2 billion and the largest positive fiscal correction was in 2019 Rp. 39.6 M. Based on the results of the analysis for the last 5 years 2014 to 2019 for PT Charoen Popkhand Indonesia Tbk, it is stated that the high or low temporary differences have no effect on earnings persistence. (2) Difference in Accounting Profit and Fiscal Profit (Permanent / Permanent Difference) at PT Charoen Popkhand Indonesia Tbk for 4 years for the largest negative fiscal correction was in 2017, namely Rp. 87.3 billion and the largest positive fiscal correction was in 2018 Rp. 38.5 M Based on the results of the analysis for the last 5 years 2014 to 2019 for PT Charoen Popkhand Indonesia Tbk stated that high or low Permanent differences have no effect on earnings persistence.